ANALISIS PENGARUH KEPUASAN DAN KEPERCAYAAN TERHADAP KOMITMEN NASABAH PADA PT. BANK PAPUA CABANG ABEPURA - Benyamin Buntu; Muhamad Ohorela (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2022)
PT. Bank Papua has a number of branch offices and units spread across various locations throughout the Land of Papua. One of them is PT. Bank Papua Abepura Branch, which is growing rapidly, is supported by customers from various backgrounds from the surrounding community. For this reason, it is necessary to provide maximum service to customers so that they provide satisfaction and create customer trust and in the end can create customer commitment to continue using the products at PT. Bank Papua Abepura Branch. The purpose of this study was to determine the partial and simultaneous effect of satisfaction and trust on customer commitment to PT. Bank Papua Abepura Branch. This study used a sample of 70 people, where all of the respondents were customers of PT. Bank Papua Abepura Branch. To collect data from respondents, the authors used a questionnaire instrument. The analytical tool used in this research is multiple linear regression. The results of the analysis show that satisfaction has a positive but not significant effect on customer commitment of PT. Bank Papua Abepura Branch. Meanwhile, trust has a positive and significant effect on customer commitment of PT. Bank Papua Abepura Branch. Simultaneously satisfaction and trust have a positive and significant impact on customer commitment of PT. Bank Papua Abepura Branch.